Trichodimerol inhibits inflammation through suppression of the nuclear transcription factor-kappaB/NOD-like receptor thermal protein domain associated protein 3 signaling pathway - Huo, Xue-Yan; Lei, Li-Rong; Guo, Wen-Xiu; Hu, Yun-Jie; Kuang, Qi-Xuan; Liu, Meng-Dan; Peng, Wan; Dai, Yi-Fei; Wang, Dong; Gu, Yu-Cheng; Guo, Da-Le; Deng, Yun (Frontiers in Microbiology, 2022)
Excessive inflammation causes chronic diseases and tissue damage. Although there has been drug treatment, its side effects are relatively large. Searching for effective anti-inflammatory drugs from natural products has become the focus of attention. First isolated from Trichoderma longibraciatum, trichodimerol is a natural product with TNF inhibition. In this study, lipopolysaccharide (LPS)-induced RAW264.7 macrophages were used as a model to investigate the anti-inflammatory activity of trichodimerol. The results of nitric oxide (NO) detection, enzyme-linked immunosorbent assay (ELISA) and reactive oxygen species (ROS) showed that trichodimerol could reduce the production of NO, ROS, and the proinflammatory cytokines interleukin (IL)-6 and tumor necrosis factor (TNF)-α. Western blotting results showed that trichodimerol could inhibit the production of inflammatory mediators such as cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) and the protein expression of nuclear transcription factor-kappaB (NF-κB), p-IKK, p-IκB, Toll-like receptor 4 (TLR4), NOD-like receptor thermal protein domain associated protein 3 (NLRP3), cysteinyl aspartate specific proteinase (Caspase)-1 and ASC, which indicated that trichodimerol may inhibit inflammation through the NF-κB and NLRP3 pathways. At the same time, molecular docking showed that trichodimerol can directly combine with the TLR4/MD-2 complex. Hence, trichodimerol inhibits inflammation by obstructing the interaction between LPS and the TLR4-MD-2 heterodimer and suppressing the downstream NF-κB and NLRP3 pathways.